Large‐Scale Assembly of Single Nanowires through Capillary‐Assisted Dielectrophoresis. (20th November 2014) - Collet, Maéva; Salomon, Sven; Klein, Naiara Yohanna; Seichepine, Florent; Vieu, Christophe; Nicu, Liviu; Larrieu, Guilhem
<x xml:space="preserve">Abstract</x> An innovative technique is proposed for the precise and scalable placement of 1D nanostructures in an affordable manner. This approach combines the dielectrophoresis phenomenon and capillary assembly to successfully align thousands of single nanowires at specific locations at the wafer. The nanowires are selectively trapped by taking advantage of the material‐specific frequence dependence. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>